2012
DOI: 10.1007/s12298-012-0115-9
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Araucaria excelsa R. Br. var. glauca Carrière from orthotropic stem explants

Abstract: The objectives of the present work were in vitro propagation of Araucaria excelsa R. Br. var. glauca Carrière (Norfolk Island pine) with focus on the evaluation of the mean number of shoots per explant (MNS/E) and mean length of shoots per explants (MLS/E) produced by different parts of the orthotropic stem of A. excelsa R. Br. var. glauca in response to plant growth regulators. Norfolk Island pine axillary meristems responded very well to the 2-iso-pentenyl adenine (2iP) and thidiazuron (TDZ) levels. Explants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The transferred DNA (T-DNA) is integrated into the plant cell genome and, in consequence, the plant produces copious growth hormones (auxins and cytokinins) and opines which are beneficial for the bacterial growth. Several authors reported successful rooting in fruit trees and woody plants when using wild strains of A. rhizogenes (Damiano and Monticelli 1998;Haggman and Aronen 2000;Sarmast et al 2012). The IAA produced by bacteria colonizing the plant rhizosphere is considered to act in conjunction with endogenous IAA in plant to stimulate root proliferation and elongation, resulting in a more branched root system architecture, which in effect enhances the host's uptake of minerals and nutrients from the soil (Spaepen et al 2007;Shokri and Emtiazi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The transferred DNA (T-DNA) is integrated into the plant cell genome and, in consequence, the plant produces copious growth hormones (auxins and cytokinins) and opines which are beneficial for the bacterial growth. Several authors reported successful rooting in fruit trees and woody plants when using wild strains of A. rhizogenes (Damiano and Monticelli 1998;Haggman and Aronen 2000;Sarmast et al 2012). The IAA produced by bacteria colonizing the plant rhizosphere is considered to act in conjunction with endogenous IAA in plant to stimulate root proliferation and elongation, resulting in a more branched root system architecture, which in effect enhances the host's uptake of minerals and nutrients from the soil (Spaepen et al 2007;Shokri and Emtiazi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have attempted to micropropagate various species of the Araucariaceae using small diameter stem segments, including Burrows et al [94] (9 Araucaria spp., 1 Agathis sp. ), Sehgal et al [102] (Araucaria columnaris), Iritani et al [60] (Araucaria angustifolia), Gough et al [103] (Agathis australis), Sarmast et al [104] (Araucaria heterophylla) and Niu et al [105] (Wollemia nobilis). These explants usually contained several nodes and internodes and buds developed from the axillary meristems.…”
Section: Conifer Micropropagationmentioning
confidence: 99%
“…Their progenitor meristems appeared to be endogenous but, as indicated above, were exogenous. Often medium to high concentrations of cytokinins, which can lead to enhanced axillary branching in dicotyledonous tree species, led to the formation of distorted buds [94,104,105]. A single bud developed in each axil.…”
Section: Conifer Micropropagationmentioning
confidence: 99%
“…Recent studies have shown development in the physicochemical characterization of its wood (McGavin et al, 2019;Fitzgerald & McGavin, 2020). The improvement of this species cultivation techniques has also been observed in different aspects (Sarmast et al, 2012;Lin et al, 2016;Matsabisa et al, 2019;Wang et al, 2020). In comparation to other more commercially valuable species such as loblolly pine and slash pine (Pinus taeda L. and Pinus elliottii, respectively), there has been less effort toward developing and deploying genetically improved and more productive individuals (Castillo et al, 2018).…”
Section: Introductionmentioning
confidence: 96%